Cmentarz wojenny Armii Radzieckiej im. Kutuzowa w Bolesławcu = War cemetery of the soviet army named after Kutuzov in Bolesławiec - Kostka, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article focuses on war graves on the territory of Bolesławiec and particularly the war cernetery named after Kutuzov in Bolesławiec. There are graves of 7 soldiers of the Armoured Corps guard and 31st Infantry Division. The monument of M.l. Kutuzov is the centre of the complex under which the sarcophagus with intestines was originally fixed.
Keywords: Armia Czerwona; cmentarze wojskowe; Bolesławiec